Tingkat stres belajar pada remeja sekolah menegah atas - Pertiwi, Eri Riana; Delianti, Nosi (Holistik Jurnal Kesehatan, 2025)
Background: Teenager is a transitional phase characterized by physical, psychological, and social changes, making individuals more vulnerable to stress, particularly related to academic demands. Unmanaged academic stress can affect students’ mental health and academic achievement. Purpose: To determine the level of academic stress among high school teenagers. Method: A quantitative approach with a descriptive design and a cross-sectional study approach was used. The study population was all 279 tenth and eleventh grade students, with a sample size of 180 students determined using the Slovin formula. The study was conducted at Teunom 1 State Senior High School, Aceh Jaya, on December 9–10, 2024. Data were analyzed using a frequency distribution. Results: The majority of respondents were 16 years old (37.3%), female (65.6%), in the tenth grade (51.7%), and had a parental income of <Rp 3,000,000 per month (62.2%). The majority of students' learning stress levels were in the moderate category, with 130 respondents (72.2%). Conclusion: The majority of students' learning stress was in the moderate category, indicating relatively high academic pressure, but still within the students' capabilities. The role of families, schools, and the social environment is needed to provide support and stress management strategies so that students can adapt positively.   Keywords: High School; Study Stress; Teenagers.   Pendahuluan: Masa remaja merupakan fase transisi yang ditandai dengan perubahan fisik, psikologis, dan sosial, sehingga rentan terhadap stres, terutama terkait tuntutan akademik. Stres belajar yang tidak terkelola dapat berdampak pada kesehatan mental dan pencapaian akademik siswa. Tujuan: Untuk mengetahui tingkat stres belajar pada remaja sekolah menengah atas. Metode: Pendekatan kuantitatif dengan desain deskriptif serta pendekatan cross sectional study. Populasi penelitian adalah seluruh siswa kelas X dan XI berjumlah 279 orang, dengan sampel 180 siswa yang ditentukan melalui rumus Slovin. Penelitian dilakukan di SMAN 1 Teunom, Aceh Jaya pada 9–10 Desember 2024. Data dianalisis secara distribusi frekuensi. Hasil: Mayoritas responden berusia 16 tahun (37.3%), berjenis kelamin perempuan (65.6%), berada di kelas X (51.7%), serta memiliki pendapatan orang tua < Rp 3,000.000 per bulan (62.2%). Tingkat stres belajar siswa mayoritas berada pada kategori sedang yaitu 130 responden (72.2%). Simpulan: Stres belajar pada siswa mayoritas berada pada kategori sedang, menunjukkan adanya tekanan akademik yang cukup tinggi, tetapi masih dalam batas kemampuan siswa. Diperlukan peran keluarga, sekolah, dan lingkungan sosial dalam memberikan dukungan serta strategi manajemen stres agar siswa mampu beradaptasi secara positif.   Kata Kunci: Remaja; Sekolah Menengah Atas; Stres Belajar.